Managing Development amidst Natural Hazards - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture (Technical Centre for Agricultural and Rural Cooperation, 2010)
If agriculture in the Caribbean is to achieve and sustain development, it must counteract these hazards through good forward planning and good practices. Widespread failure must not be tolerated (USAID-OAS, 1999)